Transitioning to online learning during the COVID-19 pandemic: differences in access and participation among students in disadvantaged school districts. Issue 2 (16th March 2021) - Catalano, Amy J.; Torff, Bruce; Anderson, Kevin S.
Abstract : Purpose: The novel coronavirus, COVID-19, which emerged in 2019 and quickly spread to the United States, resulted in widespread closure of PreK-12 schools and universities and a rapid transition to online learning. There are concerns about how students in high-needs school districts will engage with online learning, given the limited access many disadvantaged students have to Internet and computers. Accordingly, the purpose of this study is to determine teacher perceptions of students' access and participation to online learning, as well as concerns about educational outcomes among different groups of learners. Design/methodology/approach: The authors surveyed 300 K-12 teachers in NY state about the tools and accommodations they employed in their online teaching, whether their students were participating in the online learning and the reasons for their lack of participation. Findings: Respondents reported that nearly 30% of all of their students were not regularly completing their assignments. Students in high-needs districts were significantly more likely to not complete their work. Teachers reported being very concerned about their students' educational outcomes, particularly students with disabilities (SWDs) and English language learners (ELLs). Respondents also provided suggestions for improving educational access to online learning in the future. Originality/value: No published research has yet examined student compliance in online learning during an emergency and, in particular, during this unprecedented time of the COVID-19 pandemic and months-long stay-at-home orders.